Strategi Guru PAI dalam Menanamkan Karakter Religius Siswa pada Era Digital di SMP Negeri 10 Lubuk Linggau - Muhamad Akip; Fitri Yani; Alta Hairil (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2025)
The rapid advancement of digital technology has influenced education, particularly in shaping students’ religious character. In the digital era, broad access to unfiltered information often contradicts Islamic values, leading to a decline in students’ religious awareness, especially at the junior high school level. This poses a challenge for Islamic Education (PAI) teachers, as observed at SMP Negeri 10 Lubuk Linggau, where some students show decreased manners, respect, and participation in religious activities. This qualitative field research employed interviews, observations, and documentation with PAI teachers, students, the school principal, and student affairs staff. The findings reveal that teachers implement habituation and role-modeling strategies through collective prayers, congregational worship, Qur’an recitation, and regular sermons, while also utilizing digital media in teaching. School support and teacher collaboration serve as supporting factors, whereas the main obstacles include limited parental involvement, low student interest, and the influence of social media.